2018
DOI: 10.1177/1048291118763620
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Air Exposure to PCBs: Regulation and Monitoring at Five Contaminated Sites in EPA Regions 1, 2, 4, and 5

Abstract: Existing regulations seek to protect the public from exposure to polychlorinated biphenyls (PCBs) in food, water, and soil. Exposure to PCBs in ambient air has recently been given explicit consideration in the human health risk assessments that form the basis of risk management decisions at contaminated sites. The objective of this paper is to examine how ambient air exposure to PCBs is regulated and monitored at five contaminated sites in the United States. We reviewed online accessible materials (including E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Air as a source of PCB exposure was nearly completely ignored until a decade ago (Robertson and Ludewig, 2011). Indeed, recently much attention is paid to inhalation exposures to low chlorinated PCBs (Basra et al, 2018;Carpenter 2015;Lehmann et al, 2015;Marek et al, 2017). These exposures are clearly dependent on congener volatility related to boiling point.…”
Section: Discussionmentioning
confidence: 99%
“…Air as a source of PCB exposure was nearly completely ignored until a decade ago (Robertson and Ludewig, 2011). Indeed, recently much attention is paid to inhalation exposures to low chlorinated PCBs (Basra et al, 2018;Carpenter 2015;Lehmann et al, 2015;Marek et al, 2017). These exposures are clearly dependent on congener volatility related to boiling point.…”
Section: Discussionmentioning
confidence: 99%
“…A study of human post-mortem brain tissue found higher concentrations of PCB 95 in samples from patients with genetic NDDs associated with ASD as compared to neurotypical controls ( Mitchell et al, 2012 ). Contemporary human exposures occur predominantly through inhalation and diet ( Ravenscroft and Schell, 2018 ; Basra et al, 2018 ; Ampleman et al, 2015 ; Malisch and Kotz, 2014 ; Cimenci et al, 2013 ; Marin et al, 2011 ; Voorspoels et al, 2008 ; Baars et al, 2004 ), and PCBs readily cross the placenta and transfer into breast milk ( Needham et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reported TEQs are higher for PCBs from waste processing sites in Africa and Bangladesh . Average atmospheric PCB concentration at EW transect (14.8 ng/m 3 ) slightly exceeded the USEPA recommended inhalation unit risk health guideline . IT corridors yielded the highest PAH-TEQs, due to elevated concentration of three benzo PAHs (BbF, BkF and BgP) (SI Table S8).…”
Section: Resultsmentioning
confidence: 99%
“…10 Average atmospheric PCB concentration at EW transect (14.8 ng/ m 3 ) slightly exceeded the USEPA recommended inhalation unit risk health guideline. 88 IT corridors yielded the highest PAH-TEQs, due to elevated concentration of three benzo PAHs (BbF, BkF and BgP) (SI Table S8). Maximum estimated daily intake of PCBs via inhalation was at least two fold higher in the EW transect over other transects (Table S9).…”
Section: Source Receptor Modeling and Intercity Variationmentioning
confidence: 99%